Effects of clay minerals and organic matter on pore evolution of the early mature lacustrine shale in the Ordos Basin, China. (1st May 2023) - Wang, Guanping; Jin, Zhijun; Zhang, Qian; Zhu, Rukai; Tang, Xuan; Liu, Kouqi; Dong, Lin
Graphical abstract: Highlights: Organic matter controls micropore volume without influence on porosity, while thermal maturity positively affects porosity. I/S influences 20–50 nm pores, chlorite and kaolinite affect 2–5 nm pores, while illite positively contributes to all mesopores. This study shows three types of mineral transformation, smectite-illite, smectite-illite-chlorite, and anorthite/albite-to-kaolinite/illite, in the early mature lacustrine shale. Chlorite affects macropore volume, porosity, and pore throat radius. Abstract: Pores related to organic matter and clay minerals provide significant storage space for hydrocarbons in organic-rich shales. However, the pore structure evolution and its related influencing factors at the early oil window stage are unclear. This study attempts to reveal the controls of organic matter and clay minerals on the pore structure of the lacustrine organic-rich Chang 7 Shale by using thin-section observational, organic petrological, elemental, scanning electron microscopy/Energy Dispersive Spectrometer (SEM/EDS) analyses, and mineralogical analyses combined with the pore structure characterization of gas adsorption and mercury injection capillary pressure (MICP). The results show that micropores (less than 2nm) and mesopores (2–50 nm) contribute to the main storage space in organic-rich intervals of the Chang 7 Shale. Organic matter content controls the development of micro-pores while no effects on porosity in the early mature lacustrine shale. Shrinkage OM pores related to the expulsion of hydrocarbons are better developed than the complex pores and sponge pores. Total clay content is correlated with mesopores volume in organic-rich lacustrine shale. Multiple stepwise linear regression model between mesopores volume and different clay minerals shows that the pores with diameters in the ranges of 2–5 nm are controlled by illite, chlorite, and kaolinite, and the pores with diameters in the ranges of 5–10 nm and 10–20 nm are controlled by illite, while 20–50 nm pores rely on illite/smectite mixed layer (I/S) and illite. Thermal maturity shows a positive effect on pore volume and porosity. There are three types of transformations of clay minerals in lacustrine shale, including the smectite-illite conversion, smectite-illite-chlorite conversion, and anorthite/albite-to-kaolinite/illite conversion. These clay mineral conversions all show positive effects on pore volume, especially the anorthite/albite-to-kaolinite/illite conversion, while the smectite-illite conversion shows some negative effects on the connectivity of the pore system. Additionally, the control of macropore volume, porosity, and pore throat radius by chlorite cannot be ignored. The findings from this study contribute to a clear insight into the pore structure evolution of lacustrine shale.